2016
DOI: 10.1016/j.jnucmat.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stress state on the reorientation of hydrides in a zirconium alloy

Abstract: Hydride reorientation can occur in spent nuclear fuel cladding when subjected to a tensile hoop stress above a threshold value during cooling. Because in these circumstances the cladding is under a multiaxial stress state, the effect of stress biaxiality on the threshold stress for hydride reorientation is investigated using hydrided CWSR Zircaloy-4 sheet specimens containing ~180 wt. ppm of hydrogen and subjected to a two-cycle thermo-mechanical treatment. The study is based on especially designed specimens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 34 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…ppm of hydrogen; see ref. [13] for details. Two locations along the specimen gauge length were examined after a thermo-mechanical treatment: one in which only in-plane hydrides were present and another location in which out-of-plane hydrides formed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ppm of hydrogen; see ref. [13] for details. Two locations along the specimen gauge length were examined after a thermo-mechanical treatment: one in which only in-plane hydrides were present and another location in which out-of-plane hydrides formed.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that plane-stress conditions exist in the thickness direction because of the thin sheet geometry of the specimens; however, a plane-strain condition can exist as a result of biaxial tension within the plane of the sheet. Finite element analyses (FEA) were performed using ANSYS to calculate the magnitude of the local principal stresses and the corresponding stress biaxiality ratios (ζ 2 /ζ 1 ) [13] . These calculations were performed under assumptions of (a) plane stress through the thickness and (b) isotropic mechanical properties at 400 °C.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, stress generated in the pressure tube near the oxide nodule due to its formation is multiaxial as discussed in section 2.3. Cinbiz et al [44] concluded in their work, that the state of stress influences the hydride reorientation in zirconium alloys. The radial hydrides in the pressure tube end up with the formation of through thickness cracks by DHC mechanism as discussed.…”
Section: Modelling Of Radial Hydride Formationmentioning
confidence: 99%